Green Synthesis of Silver Nanoparticles using the Algae: Green Synthesis of Silver Nanoparticles using the Algae - Ali, Doaa Oday; Ali, Liqaa Oday; Ali, Samara Oday (Journal of Tropical Life Science, 2024)
Green methods of nanoparticle production have gained prominence due to their environmental and safety advantages. As reducing agents, these techniques employ biological substances, including bacteria, fungi, algae, and plants. In this study, the algae Chara vulgaris was used for the biosynthesis of silver nanoparticles as an environmentally friendly method. The synthesized nanoparticles were characterized using UV, FTIR, SEM, atomic absorption spectrometry, and zeta analysis. These nanoparticles have potential environmental applications in water treatment, especially in the removal of heavy metals such as cadmium, lead, and nickel at different concentrations (1, 3, 5, 7, and 9 ppm) over 12 and 24 hours. The results showed that lead had the highest removal rate of 99.5% for a concentration of 3 ppm at 24 hours. Cadmium showed the highest removal rate of 100% at 3 and 5 ppm concentrations at 24 h, and nickel recorded a removal rate of 83.2% for 1 ppm concentration at 24 h. This study highlights a low-cost, effective, and safer biological method with promising results in removing heavy metals from water.